Wakaf Produktif Dalam Pemberantasan Kemiskinan Melalui Pemberdayaan Ekonomi di Yayasan Nurul Hayat Surabaya - Azwar Anas; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aims to determining howthemanagement of waqf productive economic empowerment of the poor. The results showed that the Yayasan Nurul Hayat Surabaya haveconducted productive endowments that participate in empowering the poor economy in the city of Surabaya. Endowments managed productively channeled through several programs among which Matabaca and also Bunda Yatim. Economic empowerment strategy taken in the management of productive endowments made through the approach of the religious side. Before accepting funding capital endowments, beneficiaries are required to attend regular lectures held Yayasan Nurul Hayat Surabaya within a period of 1 year. Endowment fund so that recipients are not only more economically independent, but also increased in terms of religion.